KOMBINASI MODEL PBL DAN MAKE A MATCH TERINTEGRASI STEM UNTUK MENINGKATKAN MOTIVASI DAN KARAKTER WASAKA SISWA - Khalisa, Sri Indriyati; Muhsinah Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe teacher activities, to analyze activities, motivation, learning outcomes and wasaka characters (environmental care and discipline) in students using a combination model of Problem Based Learning and Make a Match integrated with STEM. This type of research is Classroom Action Research (PTK). The research subjects were VA class students of SDN Sungai Miai 5 Banjarmasin. The results showed that teacher activities were carried out to reach 88.16 with "very good" criteria, student activities were carried out to reach a percentage of 83.82% with "very active" criteria, student motivation was carried out to reach 82.35% with "very active" criteria, student cognitive learning outcomes reached a percentage of 83.80% with "complete" criteria, wasaka character assessment reached a percentage of 85.29% with "already cultured" criteria and psychomotor learning outcomes reached a percentage of 82.85% with "very good" criteria.   Keywords: make a match, motivation, wasaka character, problem based learning